383. Increased Need for Antimicrobial Stewardship during a COVID-19 Outbreak in New York City. (31st December 2020) - Policar, Maurice; Barber, Peter; Malik, Yesha
Abstract: Background: The impact of COVID-19 on the health care system in New York City (NYC) cannot be overstated. The first documented cases of COVID-19 in Queens NYC occurred in early March of 2020. The total number of patients with proven or suspected COVID-19 at Elmhurst Hospital peaked in early April. A dramatic increase in the use of antimicrobials occurred in April, and correlated with the increased number of intubated COVID-19 patients at Elmhurst Hospital. Methods: Antimicrobial Stewardship Committee activities and meetings had been suspended for the months of March and April due to the increased clinical demands associated with the COVID-19 outbreak. In preparation for the May meeting, a retrospective analysis of antimicrobial use for March and April of 2020 was performed. Results: The analysis revealed a 30% increase in the use of antimicrobials. The average total days of antimicrobials per 1000 patient days (TDA/TPD) was 445 for January through March of 2020. In April, this number climbed to 580. TDA/TPD increased from 57 to 90 (58%) for vancomycin, 25 to 35 (40%) for meropenem, and 31 to 89 (187%) for cefepime. The number of intervention by the Antibiotic Stewardship team remained low during this time period. Total Days of Antimicrobials per 1000 Patient Days (TDA/TPD) Conclusion: A dramatic increase in the use of antimicrobials correlated with an increase in the number of intubated patients at Elmhurst Hospital during a COVID-19 outbreak. It is likely that the frequent appearance of fever and leukocytosis in intubated patients with COVID-19 prompted an increase in empiric antimicrobial use. The 48 hour time outs and prospective review of antimicrobial use may be necessary to maintain stewardship efforts during the COVID-19 epidemic. Further review of antibiotic usage in critically ill COVID-19 patients is needed to help define stewardship practices as we go forward in this pandemic. Disclosures: All Authors : No reported disclosures